A man without a country - Vonnegut, Kurt 1922-2007 (Seven Stories Press, 2005)
In a collection of brief autobiographical essays, the renowned novelist offers his views on art, politics, and everyday life in America. A Man Without a Country is Kurt Vonnegut's hilariously funny and razor-sharp look at life "If I die-God forbid-I would like to go to heaven to ask somebody in charge up there, Hey, what was the good news and what was the bad news?"), art ("To practice any art, no matter how well or badly, is a way to make your soul grow. So do it."), politics ("I asked former Yankees pitcher Jim Bouton what he thought of our great victory over Iraq and he said, Mohammed Ali versus Mr. Rogers."), and the condition of the soul of America today ("What has happened to us?"). Gleaned from short essays and speeches composed over the last five years and plentifully illustrated with artwork by the author in full color throughout, A Man Without a Country gives us Vonnegut both speaking out with indignation and writing tenderly to his fellow Americans, sometimes joking, at other times hopeless, always searching.
Keywords: Vonnegut, Kurt; Vonnegut, Kurt -- 1922-2007; Geschichte 1900-2000; Politik; Authors, American -- 20th century -- Biography; USA; United States -- Politics and government -- 2001-; Biografie